Language beyond Words: The Neuroscience of Accent - Guadalupe Davila (Frontiers Research Topics, 2017)
Language learning also implies the acquisition of a set of phonetic rules and prosodic contours which define the accent in that language. While often considered as merely accessory, accent is an essential component of psychological identity as it embodies information on origin, culture, and social class. Speaking with a non-standard (foreign) accent is not inconsequential because it may negatively impact communication and social adjustment. Nevertheless, the lack of a formal definition of accent may explain that, as compared with other aspects of language, it has received relatively little attention until recently. During the past decade there has been increasing interest in the analysis of accent from a neuroscientific perspective. This e-book integrates data from different scientific frameworks. The reader will find fruitful research on new models of accent processing, how learning a new accent proceeds, and the role of feedback on accent learning in healthy subjects. In addition, information on accent changes in pathological conditions including developmental and psychogenic foreign accent syndromes as well as the description of a new variant of foreign accent syndrome is also included. It is anticipated that the articles in this e-book will enhance the understanding of accent as a linguistic phenomenon, the neural networks supporting it and potential interventions to accelerate acquisition or relearning of native accents.